(untitled) (Research, Society and Development, 2023)
The aim of this study was to analyze the barriers to changing the behavior of overweight women participating in the VAMOS 2.0 Program. Participants were 22 overweight elderly women with a mean age of 69.72±5.41 years. Baseline and post-intervention interviews of the VAMOS 2.0 program were conducted. The software NVIVO® version 12.0 was used to analyze the interviews and coding the categories: barriers to physical activity (PA) and eating behavior (EB). Lack of motivation and health problems were the main barriers to the practice of PA; changing eating habits and social support were considered barriers to changing EB at baseline. The SARS CoV-2 pandemic was cited as a barrier for the two markers in the post-intervention period, especially for PA. Barriers to PA and EB are found in elderly women participating in VAMOS. However, the COVID-19 pandemic is believed to influence these barriers to decrease motivation.